Synthesis of 2-phenoxy-2-phenylethyl acrylate and copolymerization with 2-phenylethyl acrylate: estimation of monomer reactivity ratios, thermal and optical properties - Ghorpade, Ravindra V.; Ponrathnam, Surendra; Chavan, Nayaku (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2016)
A new aromatic based monomer 2-phenoxy-2-phenylethyl acrylate (PPEA) was synthesized. Copolymers of PPEA with 2-phenylethyl acrylate (PEA) were prepared by free radical polymerization. The reactivity ratios were estimated using various graphical methods. Structural parameters of the copolymers were obtained by calculating the dyad monomer sequence fractions and the mean sequence length. Optical properties of polymers such as refractive indices and UV-Visible absorption were investigated. The glass transition temperature and thermal degradation behavior of the copolymers were studied. Combined with the RI, transparency and thermal properties, prepared copolymers hold great promise as materials for intraocular lens applications.
Keywords: 2-Phenoxy-2-phenylethyl acrylate; 2-phenylethyl acrylate; copolymerization; Optical properties; reactivity ratios; Thermal properties